2021
DOI: 10.1111/mec.16286
|View full text |Cite
|
Sign up to set email alerts
|

Venoms for all occasions: The functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function

Abstract: The phylum Cnidaria is the oldest extant venomous group and is defined by the presence of nematocysts, specialized organelles responsible for venom production and delivery. Although toxin peptides and the cells housing nematocysts are distributed across the entire animal, nematocyte and venom profiles have been shown to differ across morphological structures in actiniarians. In this study, we explore the relationship between patterns of toxin expression and the ecological roles of discrete anatomical structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 74 publications
0
46
0
Order By: Relevance
“…Columbus-Shenkar and his team study the changes of different toxin expression levels in different developmental stages of Nematostella vectensis, and suggested that venom composition changes across development and that the changes were related to the differences of interspecific interactions in its life stage (Columbus-Shenkar et al, 2018). Recent studies have found that the functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function (Ashwood et al, 2022). Because sea anemones do not have a centralized venom system, but have nematocysts distributed in the entire body, it is possible to realize the functional specialization of venom in a specific tissue based on the function of the tissue (Mccabe and Mackessy, 2015;Surm et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Columbus-Shenkar and his team study the changes of different toxin expression levels in different developmental stages of Nematostella vectensis, and suggested that venom composition changes across development and that the changes were related to the differences of interspecific interactions in its life stage (Columbus-Shenkar et al, 2018). Recent studies have found that the functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function (Ashwood et al, 2022). Because sea anemones do not have a centralized venom system, but have nematocysts distributed in the entire body, it is possible to realize the functional specialization of venom in a specific tissue based on the function of the tissue (Mccabe and Mackessy, 2015;Surm et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the model sea anemone Nematostella vectensis Stephenson, 1935 has been a recent focus for studying venom modulation, including across the life history of this species ( Columbus-Shenkar et al, 2018 ) and after exposure to abiotic stressors ( Sachkova et al, 2020 ). Several studies in other sea anemones using RNA-seq show venom expression varies across distinct tissue types ( Macrander et al, 2015 , 2016 ; Surm et al, 2019 ; Ashwood et al, 2021a , 2021b ). Although a robust pattern of toxin variation has been demonstrated in sea anemones (anthozoans), comparatively little has been explored in other cnidarians, including jellyfish and their relatives (medusozoans), despite their high developmental and ecological diversity ( Boero et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…While genomic and transcriptomic measurements can provide the copy number and expression level of a gene, respectively, the biology of a trait heavily depends on the synthesis level of the protein product of a gene. Moreover, in some cases protein levels are not in direct correlation to RNA levels and proteomic and transcriptomic dataset might give contrasting pictures (Ashwood et al, 2022; Bathke et al, 2019; Takemon et al, 2021). Thus, we tested the notion that Florida Nv1 protein levels are massively reduced using a proteomics approach, comparing samples from Florida with North Carolina, the closest population to Florida where we had genomic data.…”
Section: Resultsmentioning
confidence: 99%